Pulse 3: recover, reform, restructure. China's outward investment appetite and implications for developing countries - Beatrice Tanjangco; Yue Cao; Rebecca Nadin; Olena Borodyna; Yunnan Chen; Linda Calabrese; Lauren A. Johnston; Edmund Downie (Overseas Development Institute (ODI), 2021)
This is the third report in ODI's Economic Pulse series. Pulse 3 explores China's international economic response as it recovers, reforms, and restructures its economy amidst an uncertain global recovery. This is as China moves on from more reactive policy measures to contain the pandemic and rescue the economy towards risk management and proactive long-term planning. Among its highlights, the report takes a closer look at trade developments between China and the BRI 140, services trade, Chinese companies' public–private partnerships, debt negotiations and decision-making structures, digital infrastructure, and China's role in the rare earth elements value chain.
Keywords: 330; Economic growth; China